Proposed response assessment and endpoints for meningioma clinical trials: report from the Response Assessment in Neuro-Oncology Working Group. Issue 1 (18th August 2018) - Huang, Raymond Y; Bi, Wenya Linda; Weller, Michael; Kaley, Thomas; Blakeley, Jaishri; Dunn, Ian; Galanis, Evanthia; Preusser, Matthias; McDermott, Michael; Rogers, Leland; Raizer, Jeffrey; Schiff, David; et al.
Abstract: No standard criteria exist for assessing response and progression in clinical trials involving patients with meningioma, and there is no consensus on the optimal endpoints for trials currently under way. As a result, there is substantial variation in the design and response criteria of meningioma trials, making comparison between trials difficult. In addition, future trials should be designed with accepted standardized endpoints. The Response Assessment in Neuro-Oncology Meningioma Working Group is an international effort to develop standardized radiologic criteria for treatment response for meningioma clinical trials. In this proposal, we present the recommendations for response criteria and endpoints for clinical trials involving patients with meningiomas.